1976
DOI: 10.1007/bf00427089
|View full text |Cite
|
Sign up to set email alerts
|

Cytological findings in transrectal aspiration biopsy on hormone- and radio-treated carcinoma of the prostate

Abstract: The study reports cytological findings in 63 cases of radio- and/or oestrogen-treated carcinoma of the prostate. The different effects of therapy on the tumor cells in the cytological smear are described and discussed. An evaluation of the results, depending on the type of therapy, showed, that radio-treated tumors, due to the rapid and strong sclerosis of connective tissue, were less suitable for aspiration biopsy than hormone-treated tumors. Further, we were able to show that the effect of therapy in well-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The histological pattern of regression is marked after two weeks of treatment. The resulting changes, such as widened acinar lumina, reduced epithelial height, and vacuolized cytoplasm, are comparable to features of treated prostatic carcinomas in patients [33,34]. As shown in long-term studies, of castration, periods up to 75 days or transplantation of PC 82 into female [ l ] or castrated male mice, PC 82 does not develop a hormone-independent subline under androgen withdrawal and thus may be superior in this regards to the Dunning 3227 rat prostatic carcinoma [35].…”
Section: Discussionmentioning
confidence: 68%
“…The histological pattern of regression is marked after two weeks of treatment. The resulting changes, such as widened acinar lumina, reduced epithelial height, and vacuolized cytoplasm, are comparable to features of treated prostatic carcinomas in patients [33,34]. As shown in long-term studies, of castration, periods up to 75 days or transplantation of PC 82 into female [ l ] or castrated male mice, PC 82 does not develop a hormone-independent subline under androgen withdrawal and thus may be superior in this regards to the Dunning 3227 rat prostatic carcinoma [35].…”
Section: Discussionmentioning
confidence: 68%
“…Several authors [9][10]18,27,30,39,[42][43]47,49,55 have used FNA of the prostate to evaluate the response to hormonal treat-ment. Leinstenschneider and Nagel 39 established six grades of regression and Andersson established four grades.…”
mentioning
confidence: 99%
“…Later, this method was used in the follow-up of oestrogen-treated patients [5], Spieler et al [16], Kurth et al [10], and Leistenschneider and Nagel [12] reported a prognostic value in cytomorphologic studies on biopsy specimens after oestrogen as well as irradiation treatment of prostatic carcinoma.…”
Section: Discussionmentioning
confidence: 99%